Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Shimia fortis sp. nov., Isolated from Marine Sediment - Xiao-Yu Dong; Pei-Ran Lin; Xin-Yun Tan; Jia-Qi Li; Zong-Jun Du; Meng-Qi Ye (Current Microbiology, 2026)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Half substitution of mineral N with fish protein hydrolysate enhancing microbial residue C and N storage and climate benefits under high straw residue return - Jia Lin Wang; Xin Yu Liu; Pei Kun Jiang; Qiu Ran Yu; Qiu Fang Xu (Journal of Environmental Management, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Atmospheric microplastics at a southern China metropolis: Occurrence, deposition flux, exposure risk and washout effect of rainfall - Zhen Yuan; Chenglei Pei; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Ran Liao; Xiangrong Xu (Science of The Total Environment, 2023)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Climate variability of cold surge and its impact on the air quality of Taiwan - Chuan-Yao Lin; Shih-Chun Candice Lung; How-Ran Guo; Pei-Chih Wu; Huey-Jen Su (Climatic Change, 2009)